Pharmacological Maneuver of Mangrove Endophytic Fungi in the South China Sea – A review - Manjula Muthu Narayanan; Pooja Shivanand; Norhayati Ahmad (Journal of Tropical Biodiversity and Biotechnology, 2022)
Conventional products have a role in addressing the thriving universal demands for biologically active substances. Since the South China Sea is a prodigious province of geostrategic and mercantile importance, it meets the basic needs of people who dwell there. The South China Sea is dominant in mangrove biodiversity which, represents 11.4% of the world’s 15.5 million hectares of mangrove forest. Mangroves are harbored by multifaceted fungal communities that represent the second colossal ecological breed of marine fungi. The symbiotic association between the plants and fungi stimulates the bioactive components such as alkaloid, depsipeptides, cyclic peptides, quinone, terpenes, lactones, terpenoid, flavonoid, phenolic acid, steroids. These components have multifaceted pharmacological activities likely, anti-inflammatory, antidiabetic, anticancer, antioxidant, and antimicrobial. This review article attempts to present a piece of insightful information currently being explored on the biologically active components generated by mangrove endophytic fungi of the South China Sea.